Control of dissolved organic matter fouling ultrafiltration membrane treating a WWTP secondary effluent via multi-pretreatments. Issue 47 (7th October 2016) - Duan, Wensong; Ling, Cong; Zhang, Fangfang; Tang, Weixi; Xu, Xiaoguang
Abstract: Dissolved organic matter (DOM) has been regarded as a major organic foulant resulting in UF membrane fouling in wastewater reclamation. This study investigated the effects of multi-pretreatments, including coagulation, adsorption, and pre-oxidation, of a WWTP secondary effluent via adding Al2 (SO4 )3 /diatomite composite, FeCl3, GAC, and O3 to control DOM fouling UF membrane. Results showed the membrane fluxes increased by 18.1, 8.1, 5.3, and 0.1% and membrane resistances decreased by 58.9, 28.9, 17.8, and 2.2%, when the optimal adding dosages of Al2 (SO4 )3 /diatomite composite, FeCl3, GAC, and O3 were 400, 80, 80, and 6 mg L −1, respectively. The tests of a series of UF membranes with different pore sizes demonstrated that DOM of 10, 000–30, 000 Dalton MW in the secondary effluent was dramatically reduced by adding Al2 (SO4 )3 /diatomite composite, FeCl3, and GAC. This fractionation was mainly protein-like substances characterized by 3DEEM fluorescence spectroscopy. Additionally, adding Al2 (SO4 )3 /diatomite composite was available for removing humic acid-like substances simultaneously. Although O3 addition effectively oxidized protein-like and humic acid-like substances, it could induce the increase in DOM of <4, 000 Dalton MW up to 80.1% and triggered the UF membrane fouling. Combination of MW distribution, SEM and 3DEEM, the DOM fractionation of <6, 000 Dalton MW, mainly humic acid-like substances, easily caused UF membrane fouling. Consequently, compared with adsorption and pre-oxidation, the coagulation of Al2 (SO4 )3 /diatomite composite, the first time used for the pretreatment of DOM, was proved to be the best additive for controlling UF membrane fouling.